Efektifitas Metode Ceramah dan Small Group Discussion tentang Kesehatan Reproduksi dan Seksual Terhadap Pengetahuan, Sikap dan Perilaku Remaja: The Effectiveness of Lecture Methods and Small Group Discussions on Reproductive and Sexual Health on Adolescents' Knowledge, Attitudes and Behaviors - Aris Handayani; Abdul Latip; Kharisma Kusumaningtyas; Titi Maharrani; Ervi Husni; Domas Nurchandra Pramudianti (Gema Bidan Indonesia, 2024)
Background: adolescents are in a phase of rapid growth and development both physically, psychologically, intellectually, socially and sexually, causing great curiosity and tend to take risky attitudes without adequate consideration, which can lead to various consequences including Sexually Transmitted Infections and unwanted pregnancies.This study aims to explain the effectiveness of sexual and reproductive health education with lecture and small group discussion methods on the level of knowledge, attitudes and behavior of adolescents.Method: this study is a Quasy -Experimental Research (pre-post test control group design) with two treatment groups and one control group. A total of 68 adolescents from 135 respondents were involved using proportional random sampling method. Each group was treated with different learning methods, namely lecture method and small group discussion consisting of 68 respondents. Data collection was carried out using pre and post questionnaires, then analyzed using the Wilcoxon Signed Rank Test and Mann Whitney Test with a significant level of P, 0.005. Results: This study shows that the effectiveness of the lecture and small discussion methods are: 1) knowledge about the small group discussion method and the lecture method have the same significant value P = 0.000 (<0.05). 2) attitudes and behaviors towards the lecture method are significantly different from the Small Group Discussion method p = 0.000 (<0.05). Conclusion: This study states that the small group discussion method is better used to improve knowledge and attitudes towards sexual and reproductive health behavior in adolescents than the lecture method because in this phase it is a phase of growth in adolescents so that adolescents want to know more about sexual and reproductive health material. Keywords: Reproductive health, knowledge, behavior, adolescent, attitude